Method for designing mixing proportion of ultrahigh-performance concrete of arch rib core of concrete-filled steel tube arch bridge
Through the response surface method, the mix ratio of ultra-high performance concrete was optimized, and the problems of construction and stress performance of the core concrete of the steel pipe concrete arch bridge arch rib were solved, achieving the effects of high strength, high elastic mold and good pumping performance.
Patent Information
- Application Number
- CN202411629033.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When the span of the steel pipe concrete arch bridge arch ribs increases, when ordinary concrete or high-strength concrete is used as core concrete, the cross-sectional dimensions and self-weight of the components are too large, making construction difficult.
The response surface method is used to optimize the parameters of the water-gluing ratio, cementitious material, steel fiber, coarse aggregate and glue collection ratio of ultra-high performance concrete, and a reasonable mix ratio is designed to improve the material performance of core concrete.
It realizes that the core concrete of steel pipe has good pumping performance without high-temperature steam curing conditions, and also has the characteristics of high strength, high elastic mold, and micro-expansion. It is suitable for the construction and design requirements of steel pipe concrete arch bridges.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field The invention relates to a mix ratio design method for ultra-high performance concrete at the core of an arch rib of a steel tube concrete arch bridge. Background Art Steel tube concrete structures are widely used in the fields of construction, bridges, etc. Steel tube concrete structures are composed of two parts: steel tube and core concrete. They can give full play to the combined properties of steel and concrete and have excellent mechanical properties. Steel tube concrete arch bridges have the advantages of convenient construction, low cost, and high material strength, and have been rapidly developed in transportation infrastructure. Whether it is a steel tube concrete arch bridge or a Meilan arch bridge, the continuous increase in span has put forward higher requirements on the bearing capacity of steel tube concrete arch ribs. In engineering applications, if ordinary concrete or high-strength concrete is used as the core concrete of the arch rib, it will cause problems such as excessive cross-sectional size and self-weight of the component and difficulty in construction. To this end, the study and preparation of a core ultra-high performance concrete that simultaneously meets the construction performance and stress performance of the core concrete in the steel tube concrete arch bridge will promote the further development of steel tube concrete arch bridges.
[0003] The core ultra-high performance concrete of steel tube concrete should have good pumping performance to meet practical applications. On this basis, with high strength, high elastic modulus, micro expansion and steam-free curing as the goals, the influence of each component in the mix ratio on the core ultra-high performance concrete is analyzed, and finally the mix ratio that meets the construction and design requirements is obtained. Summary of the invention The purpose of the present invention is to provide a method for designing the mix ratio of ultra-high performance concrete for the arch rib core of a steel tube concrete arch bridge, which has a reasonable design and improves the material properties of the steel tube concrete core concrete.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is: a method for designing the mix ratio of ultra-high performance concrete for the arch rib core of a steel tube concrete arch bridge, using the response surface method to perform parameter optimization analysis on the water-binder ratio, cementitious material, steel fiber, coarse aggregate and cement-aggregate ratio of the ultra-high performance concrete, comprising the following steps: (1) With slump, expansion, and 28d compressive strength as response values, the response surface methodology was used to optimize the mix ratio of water-binder ratio and the composition of cementitious materials to obtain the optimal values of water-binder ratio and the composition of cementitious materials; (2) With slump, expansion, relative pressure water seepage rate, segregation rate, 28d compressive strength and 28d elastic modulus as response values, the response surface methodology was used to optimize the steel fiber dosage, coarse aggregate and adhesive-aggregate ratio. The optimal values of coarse aggregate replacement rate, steel fiber volume dosage and adhesive-aggregate ratio were obtained.
[0006] Furthermore, the 28d axial compressive strength test value can reach 130MPa, and the 28d elastic modulus test value can reach 48.22MPa.
[0007] Furthermore, the slump and expansion test values were 205 mm and 610 mm, respectively, and the relative pressure water seepage rate and static segregation rate test values were 27.41% and 1.07%, respectively.
[0008] Furthermore, the test values of slump, expansion, relative pressure water seepage rate, static segregation rate, 28d compressive strength and 28d elastic modulus were 230mm, 630mm, 32.2%, 1.85%, 131.5MPa and 40.3MPa, respectively. The errors between the test values of soil slump, expansion, relative pressure water seepage rate, static segregation rate, 28d compressive strength and 28d elastic modulus and the predicted values by response surface method were 2.74%, 1.80%, 4.43%, 4.51%, 4.86% and 4.69%, respectively.
[0009] Furthermore, the cement of ultra-high performance concrete is silicate cement, and the strength grade of silicate cement is P•O52.5; the silicon content of silica fume in ultra-high performance concrete is not less than 98%; S95 grade mineral powder is used in ultra-high performance concrete; the fly ash used in ultra-high performance concrete is ultra-fine fly ash; the coarse aggregate of ultra-high performance concrete is basalt crushed stone with a particle size range of 5 to 10mm; the fineness modulus of fine aggregate of ultra-high performance concrete is 2.75, and the sand is quartz sand produced by rock crushing mechanism with a particle size range of 0.15mm to 4.75mm, and the particle size of quartz powder is 0.038mm; the water reducer of ultra-high performance concrete is polycarboxylic acid high-performance water reducer with a water reduction rate of 30% and a solid content of 40%; the expansive agent of ultra-high performance concrete is calcium sulfoaluminate expansive agent.
[0010] Another technical solution adopted by the present invention is a method for preparing ultra-high performance concrete for the core of a steel tube concrete arch bridge arch rib, which adopts the above-mentioned ultra-high performance concrete mix ratio design method for the core of a steel tube concrete arch bridge arch rib to obtain the mix ratio of the ultra-high performance concrete, and the preparation method comprises the following steps: Step 1: Fully mix the cementitious material, coarse aggregate and fine aggregate according to the mix ratio, then slowly add the steel fiber and mix evenly to obtain a mixture; Step 2: Evenly mix the mixture obtained in the above step 1, the admixture and water to obtain steel fiber ultra-high performance concrete.
[0011] Compared with the prior art, the present invention has the following effects: the present invention is reasonably designed, and the steel tube concrete core steel fiber ultra-high performance concrete mix ratio designed by the response surface method can have good pumping performance without high-temperature steam curing, and at the same time has the characteristics of high strength, high elastic modulus, micro-expansion, etc.; at the same time, it is consistent with the working performance and mechanical properties of concrete in the steel tube concrete arch bridge, which is of far-reaching significance for promoting the further development of steel tube concrete arch bridges. DETAILED DESCRIPTION The present invention is further described in detail below in conjunction with specific implementation methods.
[0013] The invention discloses a method for designing a mix ratio of ultra-high performance concrete for the arch rib core of a steel tube concrete arch bridge, and aims to improve the material properties of the steel tube concrete core concrete. The response surface method is used to perform parameter optimization analysis on the water-binder ratio, cementitious material, steel fiber, coarse aggregate and binder-aggregate ratio of the ultra-high performance concrete, so as to obtain an ultra-high performance concrete mix ratio that meets the working performance of the core concrete in the steel tube concrete tube. The steel fiber-doped ultra-high performance concrete prepared according to the designed mix ratio has the characteristics of good pumping performance, high strength, high elastic modulus, micro expansion and the like, and the curing temperature is room temperature curing.
[0014] The mix design method specifically includes the following steps: (1) With slump, expansion, and 28d compressive strength as response values, the response surface methodology was used to optimize the mix design of the water-binder ratio and the composition of the cementitious materials. The optimal values of the water-binder ratio and the composition of the cementitious materials were obtained. Specifically, the water-binder ratio, cement content, silica fume content, mineral powder content, and fly ash content were 0.173, 0.641, 0.076, 0.107, and 0.126, respectively. (2) With slump, expansion, relative pressure water seepage rate, segregation rate, 28d compressive strength and 28d elastic modulus as response values, the response surface methodology was used to optimize the steel fiber dosage, coarse aggregate and adhesive-aggregate ratio. The optimal values of coarse aggregate replacement rate, steel fiber volume dosage and adhesive-aggregate ratio were obtained. Specifically, the coarse aggregate replacement rate, steel fiber volume dosage and adhesive-aggregate ratio were 0.5, 0.98% and 1.25, respectively.
[0015] In this embodiment, the 28d axial compressive strength test value of the steel fiber ultra-high performance concrete obtained by the above mix ratio design can reach 130MPa. The 28d elastic modulus test value of the steel fiber ultra-high performance concrete obtained by the above mix ratio design can reach 48.22MPa.
[0016] In this embodiment, the slump and spread test values are 205 mm and 610 mm, respectively, and the relative pressure water seepage rate and static segregation rate test values are 27.41% and 1.07%, respectively. The errors of slump, spread and 28d compressive strength with the predicted values by response surface method are only 2.49%, 2.15% and 1.61%, respectively.
[0017] In this embodiment, the test values of slump, expansion, relative pressure bleeding rate, static segregation rate, 28d compressive strength and 28d elastic modulus are 230mm, 630mm, 32.2%, 1.85%, 131.5MPa and 40.3MPa respectively. The errors between the test values of slump, expansion, relative pressure bleeding rate, static segregation rate, 28d compressive strength and 28d elastic modulus and the predicted values by response surface method are 2.74%, 1.80%, 4.43%, 4.51%, 4.86% and 4.69% respectively, indicating that the optimization of steel fiber ultra-high performance concrete mix ratio by this method has certain accuracy and high reliability.
[0018] In this embodiment, the cement of the ultra-high performance concrete is "Yangchun Shanshui" brand ordinary silicate cement, and the strength grade of silicate cement is P•O52.5; the silicon content of the silica fume of the ultra-high performance concrete is not less than 98%; the ultra-high performance concrete adopts S95 grade mineral powder; the fly ash used in the ultra-high performance concrete is ultra-fine fly ash; the coarse aggregate of the ultra-high performance concrete is basalt crushed stone with a particle size range of 5 to 10 mm; the fineness modulus of the fine aggregate of the ultra-high performance concrete is 2.75, and the sand is quartz sand produced by a rock crusher with a particle size range of 0.15 mm to 4.75 mm, and the quartz powder particle size is 0.038 mm; the water reducer of the ultra-high performance concrete is a polycarboxylic acid high-performance water reducer with a water reduction rate of 30% and a solid content of 40%; the expansion agent of the ultra-high performance concrete is a calcium sulfoaluminate expansion agent.
[0019] In this embodiment, the preparation method of the steel tube concrete arch bridge arch rib core ultra-high performance concrete adopts the above-mentioned steel tube concrete arch bridge arch rib core ultra-high performance concrete mix ratio design method to obtain the mix ratio of ultra-high performance concrete, and the preparation method comprises the following steps: Step 1: Fully mix the cementitious material, coarse aggregate and fine aggregate according to the mix ratio, then slowly add the steel fiber and mix evenly to obtain a mixture; Step 2: Evenly stir the mixture obtained in the above step 1, the admixture (polycarboxylic acid high-performance water-reducing agent and calcium sulphoaluminate expansion agent), and water to obtain steel fiber ultra-high performance concrete.
[0020] Example 1: Ultra-high performance concrete mix design based on water-binder ratio and cementitious material composition: Raw materials: (1) Cement: Use "Yangchun Shanshui" brand ordinary Portland cement with a strength grade of P•O52.5; (2) Silica fume: Select silica fume with a silicon content of not less than 98%; (3) Mineral powder: S95 mineral powder is selected, which has a higher fineness and can improve the working performance of concrete, making it easier to mix, transport and pour concrete. In addition, S95 mineral powder can reduce the amount of cement and reduce the cost of concrete without sacrificing performance; (4) Fly ash: Use ultra-fine fly ash; (5) Coarse aggregate: basalt crushed stone with a particle size range of 5 to 10 mm, an apparent density of 2730 kg / m³, a bulk density of 1690 kg / m³, a crushing value of 6.6%, and a needle-like content of 3.4%; (6) Fine aggregate: The fineness modulus is 2.75. The sand is quartz sand produced by rock crushing, with a particle size range of 0.15 mm to 4.75 mm, and the particle size of quartz powder is 0.038 mm. The proportion of each particle size is shown in Table 1; Table 1 Fine aggregate particle size and dosage (7) High-efficiency water reducer: The selected water reducer is polycarboxylic acid high-performance water reducer, with a water reduction rate of 30%, a solid content of 40%, and a dosage of 0.015; (8) Expansion agent: The expansion agent is calcium sulfoaluminate expansion agent, and the dosage is 0.05.
[0021] Preparation method: Step 1: Fully mix the cementitious material, coarse aggregate and fine aggregate according to the mix ratio design to obtain a mixture; Step 2: Evenly mix the mixture obtained in the above step 1, the admixture (polycarboxylic acid high-performance water-reducing agent and calcium sulphoaluminate expansion agent) and water to obtain ultra-high performance concrete.
[0022] Technical indicators: (1) Fluidity: The fluidity test method is carried out in accordance with the relevant provisions of the Standard for Test Methods for Performance of Ordinary Concrete Mixtures (GB / T50080-2016). The fluidity test uses a slump cone and a slump plate to test its slump and expansion; (2) Mechanical properties: The mechanical properties test method is carried out in accordance with the relevant provisions of the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T50081-2019), and its compressive strength and elastic modulus are tested; (3) Relative pressure water seepage rate: The relative pressure water seepage rate test method is carried out in accordance with the relevant provisions of the Standard for Test Methods for Performance of Ordinary Concrete Mixtures (GB / T 50080-2016), and the instrument used is the SY-3 pressure water seepage meter; (4) Static segregation rate: The test method is carried out in accordance with the relevant provisions of the Standard for Test Methods for Performance of Ordinary Concrete Mixtures (GB / T50080-2016), and the instrument uses a segregation cylinder.
[0023] Based on the water-binder ratio, silica fume content, mineral powder content, and fly ash content, a response surface design was conducted. A total of 25 groups of 27 tests were designed. To ensure the accuracy of the test, the center point was repeated three times. Table 2 shows the experimental mix design and test results.
[0024] Table 2 Results of response surface test of ultra-high performance concrete In order to obtain a mix ratio that meets the target, the response surface parameter optimization was carried out with water-binder ratio, silica fume content, fly ash content, and mineral powder content as variables, and slump, expansion, and 28d compressive strength as target optimization values. The water-binder ratio, cement content, silica fume content, mineral powder content, and fly ash content were determined to be 0.173, 0.641, 0.076, 0.107, and 0.126, respectively. Table 3 shows the test values and experimental values of the optimized ultra-high performance concrete mix ratio.
[0025] Table 3 Errors between the predicted values and actual values of UHPCC response surface optimization Example 2: Mix design of ultra-high performance concrete with steel fiber based on steel fiber, coarse aggregate and glue-aggregate ratio: The raw materials and technical indicators in this example are consistent with those in Example 1.
[0026] Preparation method: Step 1: Fully mix the cementitious material, coarse aggregate and fine aggregate according to the mix ratio design, and then slowly add the steel fiber to obtain a mixture; Step 2: Evenly mix the mixture obtained in the above step 1, the admixture (polycarboxylic acid high performance water reducing agent and calcium sulphoaluminate expansion agent) and water to obtain steel fiber ultra-high performance concrete.
[0027] Based on the response surface test design of steel fiber, coarse aggregate and adhesive-aggregate ratio, a total of 13 groups of 15 experiments were designed. To ensure the accuracy of the test, the center point was repeated three times. Table 4 shows the experimental mix design and test results.
[0028] Table 4 Response surface test results of steel fiber ultra-high performance concrete In order to obtain a mix ratio that meets the target, the response surface parameter optimization was carried out with the steel fiber volume content, adhesive-aggregate ratio and coarse aggregate replacement rate as variables, and the slump, expansion, relative pressure bleeding rate, static segregation rate, 28d compressive strength and elastic modulus as the target optimization values, and the coarse aggregate replacement material, steel fiber content and adhesive-aggregate ratio were determined to be 0.5, 0.98% and 1.25 respectively. Table 5 shows the test values and experimental values of the optimized steel fiber ultra-high performance concrete mix ratio.
[0029] Table 5 Error between the predicted value and the actual value of the response surface optimization of steel fiber ultra-high performance concrete From the above, it can be seen that the response surface method is used for mix optimization design, and the optimized mix ratio is tested. The error between the test value and the predicted value of each response value is within 5%. The mix ratio suitable for steel tube concrete steel fiber ultra-high performance concrete is obtained as shown in Table 6.
[0030] Table 6 Steel fiber ultra-high performance concrete mix ratio Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. A method for designing the mix ratio of ultra-high performance concrete for the core of a steel tube concrete arch bridge arch rib, characterized in that: The response surface methodology was used to optimize the parameters of water-binder ratio, cementitious materials, steel fiber, coarse aggregate and binder-aggregate ratio of ultra-high performance concrete, including the following steps: (1) With slump, expansion, and 28d compressive strength as response values, the response surface methodology was used to optimize the mix ratio of water-binder ratio and the composition of cementitious materials to obtain the optimal values of water-binder ratio and the composition of cementitious materials; (2) With slump, expansion, relative pressure water seepage rate, segregation rate, 28d compressive strength and 28d elastic modulus as response values, the response surface methodology was used to optimize the steel fiber dosage, coarse aggregate and adhesive-aggregate ratio. The optimal values of coarse aggregate replacement rate, steel fiber volume dosage and adhesive-aggregate ratio were obtained.
2. The method for designing the mix ratio of ultra-high performance concrete for the arch rib core of a steel tube concrete arch bridge according to claim 1, characterized in that: The 28d axial compressive strength test value can reach 130MPa, and the 28d elastic modulus test value can reach 48.22MPa.
3. The method for designing the mix proportion of ultra-high performance concrete for the core of the steel tube concrete arch bridge arch rib according to claim 1, characterized in that: The slump and expansion test values were 205mm and 610mm respectively, and the relative pressure water seepage rate and static segregation rate test values were 27.41% and 1.07% respectively.
4. The method for designing the mix proportion of ultra-high performance concrete for the arch rib core of a steel tube concrete arch bridge according to claim 1, characterized in that: The test values of slump, expansion, relative pressure water seepage rate, static segregation rate, 28d compressive strength and 28d elastic modulus were 230mm, 630mm, 32.2%, 1.85%, 131.5MPa and 40.3MPa, respectively. The errors between the test values of slump, expansion, relative pressure water seepage rate, static segregation rate, 28d compressive strength and 28d elastic modulus and the predicted values by response surface method were 2.74%, 1.80%, 4.43%, 4.51%, 4.86% and 4.69%, respectively.
5. The method for designing the mix ratio of ultra-high performance concrete for the core of the steel tube concrete arch bridge arch rib according to claim 1, characterized in that: The cement used in ultra-high performance concrete is silicate cement, and the strength grade of silicate cement is P•O52.5; the silicon content of silica fume in ultra-high performance concrete is not less than 98%; ultra-high performance concrete uses S95 grade mineral powder; the fly ash used in ultra-high performance concrete is ultra-fine fly ash; the coarse aggregate of ultra-high performance concrete is basalt crushed stone with a particle size range of 5 to 10mm; the fineness modulus of the fine aggregate of ultra-high performance concrete is 2.75, and the sand is quartz sand produced by rock crushing with a particle size range of 0.15mm to 4.75mm, and the particle size of quartz powder is 0.038mm; the water reducer of ultra-high performance concrete is polycarboxylic acid high-performance water reducer with a water reduction rate of 30% and a solid content of 40%; the expansive agent of ultra-high performance concrete is calcium sulfoaluminate expansive agent.
6. A method for preparing ultra-high performance concrete for the core of a steel tube concrete arch bridge arch rib, characterized in that: The method for designing the mix ratio of ultra-high performance concrete for the arch rib core of a steel tube concrete arch bridge as claimed in any one of claims 1 to 5 is used to obtain the mix ratio of ultra-high performance concrete, comprising the following steps: Step 1: Fully mix the cementitious material, coarse aggregate and fine aggregate according to the mix ratio, then slowly add the steel fiber and mix evenly to obtain a mixture; Step 2: Evenly mix the mixture obtained in the above step 1, the admixture and water to obtain steel fiber ultra-high performance concrete.
Citation Information
Patent Citations
Design method of ultra-high performance fiber reinforced concrete containing coarse aggregate
CN112668176A
Coarse aggregate-containing 200MPa-grade steam-curing-free ultra-high performance concrete and preparation method thereof
CN115140974A
Design method for mix proportion of sprayed recycled concrete
CN115312147A
Multi-performance prediction method of ultra-high performance concrete and mix proportion optimization design method of ultra-high performance concrete
CN115964954A
Steam-curing-free ultra-high performance concrete for bridge pier body and preparation method of steam-curing-free ultra-high performance concrete
CN116283148A
Cited By
UHPC mix proportion AI generation method and system
CN121122455A